Ley seca by Angie Cervantes: The Ordeal of a Costa Rican Teenage Girl - Miller, Elaine M. (Latin American Theatre Review, 2018)
In Angie Cervantes’s Ley seca (2007), seventeen-year-old Eva faces loneliness and social pressure as she seeks an illegal abortion. The play’s setting during Holy Week and use of the Stations of the Cross as its structural framework call attention to the ways in which the weight of the Catholic Church’s moral teachings and their influence on the legal regulation of reproductive rights in contemporary Costa Rica create obstacles for women. While Eva searches for help, she suffers the ordeal of her own Stations of the Cross, which parallel the Catholic devotion. Her agony increases as she finds her options limited by the binary relation of gender associated with compulsory heterosexuality. This article uses Judith Butler’s theory of gender as performatively constructed to examine how the dramatist subverts and dismantles the binaries linking rationality to men and nurturing roles to women. The voice-over of a thirty-year-old pregnant Eva combines with the interactions of teenage Eva with other characters to critique compulsory heterosexuality as the ideal family model in Costa Rica and propose alternative configurations of the family and accompanying gender roles.